2012
DOI: 10.1371/journal.pone.0049604
|View full text |Cite
|
Sign up to set email alerts
|

Are Long-Lasting Insecticidal Nets Effective for Preventing Childhood Deaths among Non-Net Users? A Community-Based Cohort Study in Western Kenya

Abstract: BackgroundIncreasing the distribution and use of insecticide-treated nets (ITNs) in Sub-Saharan Africa has made controlling malaria with ITNs more practical. We evaluated community effects induced by ITNs, specifically long-lasting insecticidal nets (LLINs), under ordinary conditions in an endemic malaria area of Western Kenya.MethodsUsing the database from Mbita Health and Demographic Surveillance System (HDSS), children younger than 5 years old were assessed over four survey periods. We analyzed the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…Consistent with other studies in sub-Saharan Africa, this particular age group may be less prioritized for net usage, particularly when there are not enough nets to cover all members of the household [ 20 , 48 50 ]. Though in such cases, children may still receive some residual benefit from reduced vector abundance in households with LLINs hanging [ 2 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies in sub-Saharan Africa, this particular age group may be less prioritized for net usage, particularly when there are not enough nets to cover all members of the household [ 20 , 48 50 ]. Though in such cases, children may still receive some residual benefit from reduced vector abundance in households with LLINs hanging [ 2 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Population in GW homogeneously distributed across the area. Malaria is another major health problem in this area [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was found that free mass distribution of ITNs did not influence the spatio-temporal clustering of malaria, but eliminated malaria clustering. Komazawa et al [10] investigated the effectiveness of long-lasting insecticidal nets for preventing childhood deaths among non-net users in Western Kenya. Using the database from Mbita Health and Demographic Surveillance System (HDSS), children younger than age five were assessed over four survey periods.…”
Section: Empirical Studies On Itn Usage and Health Outcomesmentioning
confidence: 99%
“…Equation (4) is the survival probability production function. The use of ITNs has been confirmed to reduce the incidence of malaria which is the principal cause of deaths among children under 5 years [6, 8, 10]. Since the focus of this paper is on under-five mortality, we measure the probability of under-five death as (1 −  π ).…”
Section: Appendixmentioning
confidence: 99%